(untitled) - The World Bank in Vietnam (WB) (Ha Noi, 2004)
The Hanoi Urban Transport Development Project includes financing of and IDA Credit and a GEF grant. The development objective of the IDA Credit is to increase urban mobility in targeted areas in Hanoi by: (i) increasing the use of public transport in two existing and one new corridors; and (ii) reducing travel times by all modes between the city center and the west and northwest sections of the city (west of West Lake). Its GEF strategic objectives are to promote a shift to more environmentally-sustainable transport modes and urban development plans, and to promote the replication of these approaches in the country and region. Its global environment objective is to lower Hanoi's transport-related greenhouse gas emissions, relative to a business-as-usual scenario. The project has three components: 1) The Bus Rapid Transit Component (BRT) will support the development of segregated bus lanes and bus priority; 2) The Road Infrastructure and Sustainable Urban Planning component includes the construction of a section of the Second Ring Road, construction of a resettlement site, and support for sustainable urban land development; and 3) The Institutional Development Component includes equipment procurement and technical assistance for various Hanoi agencies.
Keywords: Urban transportation.,Giao thông đô thị,Roads,Đuờng giao thông